2014
DOI: 10.1007/s11051-014-2670-1
|View full text |Cite
|
Sign up to set email alerts
|

The modification of structural and optical properties of nano- and submicron ZnO powders by variation of solvothermal syntheses conditions

Abstract: Nano-(30-60 nm) and submicron (100-350 nm) ZnO particles were synthesized using solvothermal method at 200°C from an ethanolic solution of zinc acetate dihydrate, applying different reaction conditions, i.e., pH value of precursor and time of the reaction. The X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), UV-vis diffuse reflectance (DR), Raman spectroscopy, and photoluminescence (PL) spectroscopy have been employed for characterization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The results showed that the average particle size distribution is about 3 nm, which is lower than the Bohr radius of ZnO (~5 nm) and confirms the preparation of quantum dots. In fact, it can be concluded that the results obtained from TEM and DLS are consistent with the results obtained from the XRD test and show the quantum dimensions and quantum confinement effects of the synthesized points 59,60,62 …”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The results showed that the average particle size distribution is about 3 nm, which is lower than the Bohr radius of ZnO (~5 nm) and confirms the preparation of quantum dots. In fact, it can be concluded that the results obtained from TEM and DLS are consistent with the results obtained from the XRD test and show the quantum dimensions and quantum confinement effects of the synthesized points 59,60,62 …”
Section: Resultssupporting
confidence: 84%
“…The average crystallite size was equal to 3 nm. 54,[59][60][61] TEM was used to study the size of quantum dots synthesized using 0.5 g of PVP40 (Qd-B), and the TEM images are shown in Figure 5A. The size of the quantum dots was between 3 and 5 nm, which is close to the crystallite size obtained by XRD.…”
Section: Absorption Of Natural Dyessupporting
confidence: 57%
See 2 more Smart Citations
“…Luković Golić et al 86 demonstrated controlled morphology of micro- and nano-sized ZnO powders using variable pH levels of lithium hydroxide (LiOH) solution to examine the effects of the solvent's pH on ZnO grain size. Firstly, the Zn particles were dissolved in ethanol/zinc acetate dihydrate solution using the sol–gel method.…”
Section: Effective Parameters On Zno Grain Sizesmentioning
confidence: 99%